2017
DOI: 10.1038/onc.2017.351
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of METTL3-mediated m6A modification in glioma stem-like cells maintenance and radioresistance

Abstract: Despite advances in biology and therapeutic modalities, existence of highly tumorigenic glioma stem-like cells (GSCs) makes glioblastomas (GBMs) invincible. N6-methyl adenosine (mA), one of the abundant mRNA modifications catalyzed by methyltransferase-like 3 and 14 (METTL3/14), influences various events in RNA metabolism. Here, we report the crucial role of METTL3-mediated mA modification in GSC (neurosphere) maintenance and dedifferentiation of glioma cells. METTL3 expression is elevated in GSC and attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
469
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(502 citation statements)
references
References 51 publications
14
469
0
Order By: Relevance
“…However, recently, Visvanathan et al. have discovered powerful but opposite evidence that METTL3‐mediated m 6 A modification was required for GSCs maintenance 48. The underlying mechanism here is controversial with what we discussed above.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 71%
“…However, recently, Visvanathan et al. have discovered powerful but opposite evidence that METTL3‐mediated m 6 A modification was required for GSCs maintenance 48. The underlying mechanism here is controversial with what we discussed above.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 71%
“…In addition, CDF analysis of AUF1 and HuR target mRNAs (Mukherjee et al., 2011; Yoon et al., 2014) from MeRIP‐seq and total RNA‐seq data has shown that AUF1 and HuR target RNAs are downregulated further than nontarget mRNAs once they are methylated (Figure 3f,g, Figures S2 and S3). These results imply possible involvement of AUF1 and HuR in the stability regulation of m6A‐modified RNA (Visvanathan et al., 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Dynamic regulation of m6A modification and mRNA decay is also dictated by position‐specific m6A methylation within the mRNA, and presence/activity of m6A‐binding proteins within a given context (Alarcón et al., 2015; Wang & He, 2014; Wang et al., 2014, 2015). A possibility is that DROSHA mRNA methylation is maintained by the presence of m6A readers or m6A‐regulated factors such as HuR, FMR1, and G3BP, resulting in preservation of DROSHA mRNA levels during the aging process (Edupuganti et al., 2017; Visvanathan et al., 2017). This may explain why DROSHA mRNA levels did not change despite having higher methylation levels compared with AGO2 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…As the critical m6A methyltransferase, the role of METTL3 in tumours is controversial. Some studies reported that METTL3 played an oncogenic role in myeloid leukaemia, liver cancer, breast cancer, glioblastoma, bladder cancer and lung cancer . Other studies indicated that METTL3 played a tumour suppressor in renal cell carcinoma and glioblastoma .…”
Section: Introductionmentioning
confidence: 99%
“…23 Recent studies showed that m6A modification played essential roles in tissue development, stem cell formation and differentiation, 24,25 control of heat shock response 26 and circadian clock controlling, 27 as well as in tumours formation. [28][29][30][31][32][33][34][35] As the critical m6A methyltransferase, the role of METTL3 in tumours is controversial.…”
Section: Introductionmentioning
confidence: 99%